2009
DOI: 10.1016/j.ccr.2009.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic Function of the Retinoblastoma Tumor Suppressor Protein

Abstract: SUMMARY The retinoblastoma protein (pRB) tumor suppressor blocks cell proliferation by repressing the E2F transcription factors. This inhibition is relieved through mitogen-induced phosphorylation of pRB, triggering E2F release and activation of cell cycle genes. E2F1 can also activate pro-apoptotic genes in response to genotoxic or oncogenic stress. However, pRB’s role in this context has not been established. Here we show that DNA damage and E1A-induced oncogenic stress promotes formation of a pRB-E2F1 compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
146
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(156 citation statements)
references
References 40 publications
8
146
2
Order By: Relevance
“…A recent work showed that pRb participates (even in its phosphorylated form) to form a transcriptionally active complex with E2F-1 to regulate expression of pro-apoptotic genes. 40,41 Our data are mostly consistent with these data, as they show that, upon ABT-737 treatment, pRb interacts with E2F-1, is recruited to both noxa and p73 promoters and contributes to Noxa expression and to cell death induction, contrary to current understanding of the regulation of E2F-1 by pRb. Strikingly, our data establish that caspase cleavage of pRb may favor these molecular events.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…A recent work showed that pRb participates (even in its phosphorylated form) to form a transcriptionally active complex with E2F-1 to regulate expression of pro-apoptotic genes. 40,41 Our data are mostly consistent with these data, as they show that, upon ABT-737 treatment, pRb interacts with E2F-1, is recruited to both noxa and p73 promoters and contributes to Noxa expression and to cell death induction, contrary to current understanding of the regulation of E2F-1 by pRb. Strikingly, our data establish that caspase cleavage of pRb may favor these molecular events.…”
Section: Discussionsupporting
confidence: 86%
“…38 By contrast, recent data showed that hyperphosphorylated pRb can maintain an interaction with E2F-1 39 and that pRb may also function, in certain instances, as a binding partner for E2F-1 to positively upregulate pro-apoptotic genes, such as p73. 40,41 To further understand how, upon ABT-737 treatment, E2F-1 and pRb contribute to induce Noxa expression and cell death, we studied the interactions between E2F-1 and the forms of pRb, in addition to their individual and combined presence on the noxa promoter.…”
mentioning
confidence: 99%
“…This suggests that, in cisplatin-resistant cells and PCAF-overexpressing cells, the PCAF-inducing apoptosis system may be abolished, regardless of p53 expression, or suppressed by an antiapoptotic gene such as Survivin. It has been shown that E2F1 can activate the expression of proapoptotic genes (30,(32)(33)(34)(35)(36). However, we did not observe increased expression of the proapoptotic gene p73, which is an E2F1 target gene, in either cisplatinresistant cells or PCAF-overexpressing cells (Fig.…”
Section: Pcaf-overexpressing Cells (contrasting
confidence: 42%
“…[111][112][113] Although a pro-apoptotic function has been reported, 114,115 many studies have found loss of RB function to enhance apoptosis due to inappropriate S-phase control, [116][117][118] causing increased sensitivity to taxanes as well as platinum compounds in different cell lines. 119,120 In contrast, p53-induced apoptosis in response to doxorubicin and combined treatment with metotrexat and 5-fluorouracil has been found to be blunted following RB knockdown in different cell lines.…”
Section: Tp53 Analogues Tp63 and Tp73mentioning
confidence: 99%